E-LEARNING: WHAT IS IT? WHERE AND HOW DO WE USE IT? IS IT EFFECTIVE? - Patridge, Martyn R (Journal of Postgraduate Medical Institute, 2011)
The term e-learning would not have been known a few decades ago and it is variously defined. Essentially e-learning includes multiple modalities of learning opportunities including computer assisted instruction, internet based learning, distance learning and use of computers to deliver stand alone learning materials which often involve multimedia techniques and varying degrees of self assessment. More recently the term blended learning has been introduced and blended learning incorporates an appreciation as to how one uses e-Learning in conjunction with more traditional methods, which in medicine would involve everything from didactic lectures to apprenticeship, small group working , clinical seminars and bedside teaching. What we now have to address is why we within medicine would be interested in e-learning and to strategically think through its role and merits. In postgraduate situations trainees increasingly have the benefit of a structured residency programme.These utilises a variety of learning opportunities but frequently involve day release and the opportunity to attend lectures and seminars. However the pressures upon clinical trainees to deliver service and the problems of shift working means that not all trainees can attend training opportunities and a facility which permits some of this training to be delivered in a self directed manner, undertaken at the trainees own rate, at a time to suit them and in an environment to suit them would be advantageous. For more senior colleagues there is increasing need to be able to demonstrate that one is remaining up to date, and over a forty year professional career the challenges and advances of medicine make this imperative. Many of us now spend a sizable amount of our working time dealing with diseases which we not even aware of in medical school. For this purpose as well, learning opportunities that can be fitted into an increasingly busy professional life are essential.